TANGGUNG JAWAB DIREKSI ATAS PERBUATAN YANG DILAKUKAN OLEH DIREKTUR OPERASIONAL PADA SUATU PERSEROAN TERBATAS (STUDI KASUS PUTUSAN MAHKAMAH AGUNG RI NOMOR 294 K/PID.SUS/2018 - Wijaya, Wilson; Nurbaiti, Siti (Tribuere, 2023)
A Limited Liability Company is a legal entity which is a capital partnership, in the process it is established based on an agreement, which conducts business activities with an authorized capital which is entirely divided into shares and fulfills the requirements stipulated by Law Number 40 of 2007 concerning Limited Liability Companies (UU PT). The management of the company by the directors does not only refer to what has been regulated in the Company Law but must also be guided by the company's articles of association. Management of the company by the directors must be based on good faith. If it turns out that the management of the company by the directors is not based on good faith, causing losses to the company, then the directors are personally responsible for the company's losses, both criminally and civilly. The problem in this research is, How is the arrangement of directors' responsibilities towards a Limited Liability Company? And what is the decision of the Supreme Court of the Republic of Indonesia Number 294 K/Pid. Sus/ 2018 December 3, 2018 is in accordance with the applicable regulations? The problem approach used is a normative juridical approach to the problem. This research is legal research that is descriptive in nature. The materials used in the preparation of this thesis are Primary Legal Materials such as: the 1945 Constitution of the Republic of Indonesia and Law Number 40 of 2007 concerning Limited Liability Companies. Secondary Legal Materials Secondary legal materials are legal publication materials that are not official documents. Tertiary Legal Materials, namely materials that provide information on primary legal materials and secondary legal materials such as dictionaries and encyclopedias, popular magazines, newspapers and other scientific journals. The conclusion of this thesis is that Tukiman Kijah's actions are personal responsibility, because he does not comply with the Business Judgment Rule doctrine as stipulated in Article 97 paragraph (5), due to losses suffered by PT. BCMG TANI BERKAH was caused by Tukiman Kijah's mistakes and negligence as a Director.